The characterization of GTP Cyclohydrolase I and 6-Pyruvoyl Tetrahydropterin Synthase enzymes as potential anti-malarial drug targets - Khairallah, Afrah Yousif Huseein (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology)
Malaria remains a public health problem and a high burden of disease, especially in developing countries. The unicellular protozoan malaria parasite of the genus Plasmodium infects about a quarter of a billion people annually, with an estimated 409 000 death cases. The majority of malaria cases occurred in Africa; hence, the region is regarded as endemic for malaria. Global efforts to eradicate the disease led to a decrease in morbidity and mortality rates. However, an enormous burden of malaria infection remains, and it cannot go unnoticed. Countries with limited resources are more affected by the disease, mainly on its public health and socio-economic development, due to many factors besides malaria itself, such as lack of access to adequate, affordable treatments and preventative regimes. Furthermore, the current antimalarial drugs are losing their efficacy because of parasite drug resistance. The emerged drug resistance has reduced the drug efficacy in clearing the parasite from the host system, causing prolonged illness and a higher risk of death. Therefore, the emerged antimalarial drug resistance has hindered the global efforts for malaria control and elimination and established an urgent need for new treatment strategies. When the resistance against classical antimalarial drugs emerged, the class of antifolate antimalarial medicines became the most common alternative. The antifolate antimalarial drugs target the malaria parasite de novo folate biosynthesis pathway by limiting folate derivates, which are essential for the parasite cell growth and survival. Yet again, the malaria parasite developed resistance against the available antifolate drugs, rendering the drugs ineffective in many cases. Given the previous success in targeting the malaria parasite de novo folate biosynthesis pathway, alternative enzymes within this pathway stand as good targets and can be explored to develop new antifolate drugs with novel mechanisms of action. The primary focus of this thesis is to contribute to the existing and growing knowledge of antimalarial drug discovery. The study aims to characterise the malaria parasite de novo folate synthesis pathway enzymes guanosine-5'-triphosphate (GTP) cyclohydrolase I (GCH1) and 6-pyruvoyl tetrahydropterin synthase (PTPS) as alternative drug targets for malaria treatment by using computational approaches. Further, discover new allosteric drug targeting sites within the two enzymes' 3D structures for future drug design and discovery. Sequence and structural analysis were carried out to characterise and pinpoint the two enzymes' unique sequence and structure-based features. From the analyses, key sequence and structure differences were identified between the malaria parasite enzymes relative to their human homolog; the identified sites can aid significantly in designing and developing new antimalarial antifolate drugs with good selectivity toward the parasites' enzymes. GCH1 and PTPS contain a catalytically essential metal ion in their active site; therefore, force field parameters were needed to study their active sites accurately during all-atom molecular dynamic simulations (MD). The force field parameters were derived through quantum mechanics potential energy surface scans of the metals bonded terms and evaluated via all-atom MD simulations. Proteins structural dynamics is imperative for many biological processes; thus, it is essential to consider the structural dynamics of proteins whilst understanding their function. In this regard, the normal mode analysis (NMA) approach based on the elastic network model (ENM) was employed to study the intrinsic dynamics and conformations changes of GCH1 and PTPS enzymes. The NMA disclosed essential structural information about the protein's intrinsic dynamics and mechanism of allosteric modulation of their binding properties, further highlighting regions that govern their conformational changes. The analysis also disclosed hotspot residues that are crucial for the proteins' fold stability and function. The NMA was further combined with sequence motif results and showed that conserved residues of GCH1 and PTPS were located within the identified key structural sites modulating the proteins' conformational rearrangement. The characterized structural features and hotspot residues were regarded as potential allosteric sites of important value for the design and development of allosteric drugs. Both GCH1 and PTPS enzymes have never been targeted before and can provide an excellent opportunity to overcome the antimalarial antifolate drug resistance problem. The data presented in this thesis contribute to the understanding of the sequence, structure, and global dynamics of both GCH1 and PTPS, further disclose potential allosteric drug targeting sites and unique structural features of both enzymes that can establish a solid starting point for drug design and development of new antimalarial drugs of a novel mechanism of actions. Lastly, the reported force field parameters will be of value for MD simulations for future in-silico drug discovery studies involving the two enzymes and other enzymes with the same Zn2+ binding motifs and coordination environments. The impact of this research can facilitate the discovery of new effective antimalarial medicines with novel mechanisms of action.
Keywords: Antimalarials; Plasmodium falciparum; Malaria -- Chemotherapy; Malaria -- Africa; Drug resistance; Drug development; Molecular dynamics